PERANCANGAN APLIKASI PEMBELAJARAN BIOLOGI KELAS XI IPA DI SEKOLAH LANJUTAN TINGKAT ATAS BERBASIS ANDROID - Fauzan Jamza; Titi Sriwahyuni; Yeka Hendriyani (Universitas Negeri Padang, 2015)
The background of the problem of this final task is due to the developments in technology and mobile phone or smartphone and also operating system in smartphone itself, such as Android. This design aims to make a mobile learning system design of Human Digestive System for science class at XI grade of Senior High School with android based. It is preferably in the learning process of biology, where the material is memorization. In spite of that, the lack of media used often makes children feel bored in studying biology.This final project was designed with language modeling software with object-oriented programming method which uses a modeling language Unified Modeling Language (UML). The programming language used was Java by using the Eclipse IDE. Trials have been conducted on the 2.2 emulator, while the implementation of the program is done on the Samsung Galaxy Young with Android 4.0.1. In general, the results that are displayed on the emulator and Young galaxy is not much different,but Android with a higher version has faster access speed . Keywords: M_Learning, Biology Android based.